Repositioning SOZECOM, Nigeria for Navigating the Digital Economy - Muhammad Lawal Maidoki (International Journal of Zakat, 2018)
Sokoto State Zakat and Waqf (Endowment) Commission aims to eradicate extreme poverty among the poor, vulnerable and mostly rural people inhabiting Sokoto state in North-western Nigeria. To achieve this aim, SOZECOM is currently restructuring its zakat, waqf and general administration processes. Part of the restructuring is the need to utilize the extensive network of paid and volunteer personnel, vast amount of data and several collaborative efforts with other institutions inorder to explore the potentials of digital finance in the administration of zakat and waqf. A major constraint toward the realization of this aim is limited digital capability. As a first imperative the need to develop SOZECOM’s institutional capacity through the strengthening of its digital capabilities was identified. This paper outlines the framework for building the capabilities needed to successfully navigate the digital economy and align its operations toward such realization